Etnis Tionghoa Dalam Dinamika Masyarakat Kepulauan Kei - Pattiasina, Johan (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2020)
This research is entitled Ethnic Chinese in the Dynamics of the Kei Islands Community. The problems that will be studied in this study are as follows: 1) How is the process of entering the Chinese community in the Kei Islands? 2) How is the interaction between the Chinese community and the local community in the Kei Islands? To get answers to these problems, the research method used is history, which consists of our stages, namely heuristics, verification, interpretation, and historiography, using theories and other relevant social science concepts. The objectives of this study are To explain the process of the arrival of the Chinese community in the Kei Islands, their interaction with the local community, and their role in the governmental, economic and socio-cultural aspects of the Kei Islands. Thus, it is hoped that this research can enrich the historiography of the Kei ethnic Chinese in Maluku, which is still relatively small. From this research, it is known that the Chinese people in the KeiIslands have existed for a long time and can interact with local communities well. It can be seen from the Chinese community's use of the indigenous Kei clan and the application of local culture in their lives, even though these practices go hand in hand with the original Chinese traditions. Until now, the Chinese community has played a vital role in various sectors of life in Kei, both in the economy and politics. It can be seen from the Chinese title Kei, and some politicians of Chinese descent, even the former regent of the Kei Islands, are of Chinese descent. Thus, the Chinese people in Kei considered themselves as Kei people.